2017
DOI: 10.1088/1361-6528/aa52e4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the elastic and fracture properties of boronitrene and molybdenum disulfide and those of graphene

Abstract: A consistent set of 2D elastic and fracture properties of hexagonal boron nitride (h-BN) monolayers (boronitrene) and molybdenum disulfide (MoS) nanosheets is derived. Reported literature values for Young's moduli and fracture strengths, based on experiments and DFT calculations, were used to estimate the line or edge energy with a local 2D bond-breaking model. Consistent information was obtained for intrinsic fracture properties. The basic mechanical properties of boronitrene are roughly 25% lower than the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…At the atomic scale, first-principles calculations have shown that the anisotropic edge energies are critical to the island morphology evolution of MoS 2 10 and h-BN. 11 The Reactive Force Field (ReaxFF) Method 12 has been applied to revealing the chemical reaction mechanisms and pathways of forming the 2D materials from the gas/powder precursors, [13][14][15] and predicting the growth morphologies of a few islands. The kinetic Monte Carlo (KMC) method has also been coupled with first-principles calculations to predict the island growth morphology as a function of flux and precursor stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…At the atomic scale, first-principles calculations have shown that the anisotropic edge energies are critical to the island morphology evolution of MoS 2 10 and h-BN. 11 The Reactive Force Field (ReaxFF) Method 12 has been applied to revealing the chemical reaction mechanisms and pathways of forming the 2D materials from the gas/powder precursors, [13][14][15] and predicting the growth morphologies of a few islands. The kinetic Monte Carlo (KMC) method has also been coupled with first-principles calculations to predict the island growth morphology as a function of flux and precursor stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed discussion of the fracture toughness of graphene has been provided recently. 4,10 Its mean value of K IC ¼ 1.1 Â 10 À3 N m À1/2 is used here for calibration of the strength ratios. Table 3 displays the toughnesses of the other group members obtained with the ratios of the fracture strengths.…”
Section: Resultsmentioning
confidence: 99%
“…Other hexagonal graphene-like 2D materials, including boronitrene [98], phosphorene [91], and silicene [11,99] containing preexisting cracks, behave in a similar way under a tensile load. These single-layer materials fail in a brittle way, and their failure is governed by the strength of the atomic bonds at the crack tip.…”
Section: Mechanical Failure Due To Grain Boundary the Role Ofmentioning
confidence: 95%
“…These single-layer materials fail in a brittle way, and their failure is governed by the strength of the atomic bonds at the crack tip. Similar to graphene, the ZZ direction is the preferable direction of crack propagation in these materials, which indicates that the bonds in the AC direction have the stronger capability to resist crack propagation than the ZZ direction [21,78,[98][99][100].…”
Section: Mechanical Failure Due To Grain Boundary the Role Ofmentioning
confidence: 99%